Earning Per Share, Debt To Equity Ratio dan Price Earning Ratio terhadap Harga Saham pada Perusahaan Farmasi di BEI - Ibel Salaste; Siti Nurlaela; Suhendro Suhendro (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2021)
The development of the health world will certainly have a positive impact for shareholders especially in pharmaceutical companies, this is reflected by the Government's support that provides ease and incentives in the form of tax deductions and import duties borne by the Government to attract investments. With these opportunities will certainly affect the price of stocks in pharmaceutical companies including the financial performance. Financial performance can be seen from several financial ratios, earning per share, debt to equity, and price earning ratio. Samples on this study were as many as 7 companies for 5 years so in 35 can sample. The results of this study simultaneously all variables in this study have an effect on the stock price. Both EPS and PER variables affect the stock price, while the DER variables negatively affect the share price.